Effects of cold storage and freezing on sheep’s milk - NESPOLO, Cássia Regina; MUNIEWEG, Félix Roman; MARCELINO, Alexandre Henrique; ARAÚJO, Luana Caroline Souza Rosa; ARAUJO, Denise Nunes; STEFANI, Lenita de Cássia Moura (Food Science and Technology, 2024)
Sheep’s milk production in Brazil is focused on the industrialization of high added value derivatives. Some factors, such as seasonal production, short lactation period, and microbiological contamination, cause a shortage of this raw material throughout the year. It is well known that low temperatures are used in the conservation of dairy products and the objective of this study was to verify the microbiological and physical-chemical quality in refrigerated and frozen raw sheep’s milk. Standard plate counts, psychrotrophics, Staphylococcus aureus, total coliforms, and fecal coliforms, as well as titratable acidity, pH, and water activity were analyzed in samples 1 day after refrigeration and 8 and 15 days after freezing temperatures. Overall, the results of refrigerated milk were based on the legislation, but frozen milk showed high values of aerobic plate, S. aureus, and acidity, especially after 15 days of storage. Psychrotrophics and coliform counts were also high, indicating a risk for the quality of the raw milk and derivatives, which emphasizes the importance of handler training for good practices in the farm, as well as in the dairy industry. Freezing may be a viable strategy; however, additional studies testing lower temperatures and previous milk pasteurization are necessary to guarantee milk quality and consumer safety.